Light-controlled active release of photocaged ciprofloxacin for lipopolysaccharide-targeted drug delivery using dendrimer conjugates. Issue 68 (1st August 2016) - Wong, Pamela T.; Tang, Shengzhuang; Mukherjee, Jhindan; Tang, Kenny; Gam, Kristina; Isham, Danielle; Murat, Claire; Sun, Rachel; Baker, James R.; Choi, Seok Ki
Abstract : We report a light-controlled release mechanism for photocaged ciprofloxacin nanoconjugate. Validation of this bacteria-targeted strategy adds a novel modality to light-based therapies for wound treatments. Abstract : We report an active delivery mechanism targeted specifically to Gram(−) bacteria based on the photochemical release of photocaged ciprofloxacin carried by a cell wall-targeted dendrimer nanoconjugate.